Axial compressive behaviours of steel–concrete-steel sandwich composite walls with novel enhanced C-channels. (December 2020) - Yan, Jia-Bao; Chen, Anzhen; Wang, Tao
Abstract: This paper developed novel steel–concrete-steel sandwich composite walls (SCSSCWs) with enhanced C-channels (SCSSCW-ECs), and studied their compressive behaviours through seven axial compression tests. The studied parameters include layout of C-channels in SCSSCWs, faceplate thickness, strength of concrete core, vertical and horizontal spacing of C-channels. Test results exhibited a three-stage working mechanism for SCSSCW-ECs under compression. Experimental observations also showed that under axial compression SCSSCW-ECs failed in concrete core crushing and local buckling of faceplate. The test results also offer useful information on the mechanism and influences of these studied parameters on axial compressive behaviours of SCSSCW-ECs. The layout of novel ECs in SCSSCW-ECs was finally optimized including layout of C-channels as well as their spacings. This paper also developed theoretical models and modified code equations in AISC, CECS, and Eurocode 4 to estimate ultimate compressive resistance of SCSSCW-ECs. These models have been validated by reported 11 test results. The validations showed that developed theoretical models offered the most accurate predictions on ultimate compressive resistance of SCSSCW-ECs.